2004
DOI: 10.1007/s00213-003-1636-2
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic/glutamatergic interactions: the effects of mGlu 2/3 receptor ligands in rats trained with LSD and PCP as discriminative stimuli

Abstract: These data, obtained using a stimulus control model of the hallucinogenic effects of PCP and LSD, provide support for the hypothesis that glutamate release is a factor in hallucinogenesis by both 5-HT(2) agonists and non-competitive NMDA antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 55 publications
4
53
5
Order By: Relevance
“…Contrary to these predictions and previous work by Winter et al (2004), the (À)-DOB discriminative stimulus, a 5-HT 2A receptor-mediated behavior, is not modulated by compounds acting at mGlu2/3 receptors. A wide range of mGlu2/3 receptor agonist and antagonist doses tested at multiple times fail to alter the discriminative stimulus effect of (À)-DOB.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to these predictions and previous work by Winter et al (2004), the (À)-DOB discriminative stimulus, a 5-HT 2A receptor-mediated behavior, is not modulated by compounds acting at mGlu2/3 receptors. A wide range of mGlu2/3 receptor agonist and antagonist doses tested at multiple times fail to alter the discriminative stimulus effect of (À)-DOB.…”
Section: Discussioncontrasting
confidence: 99%
“…A wide range of mGlu2/3 receptor agonist and antagonist doses tested at multiple times fail to alter the discriminative stimulus effect of (À)-DOB. Winter et al (2004) found that in rats the LSD discriminative stimulus was subtly potentiated by an mGlu2/3 antagonist and attenuated by an mGlu2/3 agonist. However, several experimental variables differ between that work and the present study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Discrimination training was then begun. The initial group of 12 subjects was trained to discriminate PCP (3.0 mg/kg, 30 min pretreatment time, IP; N = 12) from vehicle as described previously (Hirschhorn and Winter 1971;Fiorella et al 1995;Winter et al, 2004). Subsequently, a second group of 12 subjects was trained at a dose of 2.5 mg/kg using a pretreatment time of 15 min (West et al 2000).…”
Section: Training Proceduresmentioning
confidence: 99%